2011
DOI: 10.1177/003335491112600211
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Risk Factors and Possible Mediation Effects in Posttraumatic Depression and Posttraumatic Stress Disorder Comorbidity

Abstract: Our data support the premise that PTSD and depression are different responses to trauma with unique risk factors. The data also suggest a hypothesis that PTSD mediates the relationship between early WTC arrival and depression, while depression mediates the relationship between alcohol use and PTSD, a more complex relationship than shown in previous studies. Clinicians should consider these factors when evaluating patients for depression and PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 42 publications
5
58
1
Order By: Relevance
“…Consistent with our EMS findings, previous 9/11 health studies found increased risks among WTC-exposed cohorts for aerodigestive conditions such as GERD6 and asthma,5 as well as for symptoms indicative of PTSD,7 depression,8 and harmful alcohol use 9. Unlike prior studies, ours is the first to concentrate on EMS workers, especially important as we used confirmed physician diagnoses from FDNY medical records rather than self-reports to describe the post-9/11 cumulative incidence of physical health conditions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with our EMS findings, previous 9/11 health studies found increased risks among WTC-exposed cohorts for aerodigestive conditions such as GERD6 and asthma,5 as well as for symptoms indicative of PTSD,7 depression,8 and harmful alcohol use 9. Unlike prior studies, ours is the first to concentrate on EMS workers, especially important as we used confirmed physician diagnoses from FDNY medical records rather than self-reports to describe the post-9/11 cumulative incidence of physical health conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Rescue and recovery workers included first responders—firefighters, police officers and emergency medical service (EMS) workers—as well as operating engineers, iron workers, railway tunnel workers, sanitation workers, utility workers, and volunteers 1. Previous research has documented an array of WTC-related physical and mental health issues among these workers including: excess cancer risks;2–4 elevated rates of aerodigestive illnesses such as asthma5 or gastroesophageal reflux disease (GERD);6 and, increased risks of post-traumatic stress disorder (PTSD),7 depression,8 and frequent binge drinking 9. Substantial comorbidities between these health conditions were also found 10 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis that relief workers' experience of difficulties is associated with mission duration was supported. Several studies have focused on the association between disaster phase (i.e., arrival time after disaster) and mental health problems (Chiu et al, 2011;Pietrzak et al, 2012). Conversely, another study has suggested that spending a longer duration on a disaster site generally appeared to be a risk factor for poor mental health (Brooks, Dunn, Amlot, Greenberg, & Rubin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, more than half of all survivors of both the Oklahoma City bombing and the WTC attacks who met criteria for PTSD were also identified as having major depression (20,55). Chiu and colleagues (15) describe three potential explanations for the high prevalence of PTSD and depression comorbidity following a traumatic event such as a disaster: Both disorders are psychological consequences of traumatic exposure, suffering with PTSD brings on secondary depression, and symptoms that characterize the two conditions overlap (15). Those with comorbid psychological disorders are generally more impaired than those with only one condition and are at greater risk for chronic disorder (42,69).…”
Section: Comorbiditymentioning
confidence: 99%